40 Right ventricular high septal pacing vs. right ventricular apical pacing following av node ablation: 20 years follow up. (5th June 2017) - Eysenck, William; Veasey, Rick; Gallagher, Angela; Jouhra, Fadi; Patel, Nikhil; Furniss, Steve; Sulke, Neil
Abstract : Introduction: Right ventricular septal (RVS) pacing is often recommended as a more physiological alternative to right ventricular apical (RVA) pacing. Most comparisons between the two sites have had short follow up and few trials have assessed the different pacing sites following atrioventricular node (AVN) ablation. We analysed 200 consecutive patients (pts) aged 66–96 (51% male) who underwent implantation of a pacemaker prior to AVN ablation with either RVA- or RVS-pacing between 1996 to 2016. Methods: All hospital notes were retrieved and reviewed. Radiographic data for the site of V lead, all hospitalisations, change in echocardiography ejection fraction (EF), QRS width trend and lead parameters were collated. All pts additionally underwent dyssynchrony echocardiography. Results: See tables 1 and 2. Conclusions: (i) EF of less than 40%; (ii) prior diagnosis of IHD and (iii) dilated cardiomyopathy independently predict HF admission following AVN ablation. However, there was no decrease in EF and no difference in inter-ventricular or intra-ventricular dyssynchrony with either pacing site after up to 20 year follow up. There was a decreased mortality rate with RVA pacing following AVN ablation after longterm follow up. We now prophylactically use CRT pacing in all pts with EF 40% and known IHD. Their outcome is part of ongoing follow up.